Antioxidant peptides from Antarctic Krill (Euphausia superba) hydrolysate: Preparation, identification and cytoprotection on H2O2-induced oxidative stress - Yue-Zhen Wang; Yu-Qin Zhao; Yu-Mei Wang; Wen-Hao Zhao; Peng Wang; Chang-Feng Chi; Bin Wang (Journal of Functional Foods, 2021)
The aim of this study was to purify and identify antioxidant peptides from Antarctic Krill hydrolysate and elucidate their cytoprotection mechanisms on H2O2-induced oxidative stress in Chang liver cells. Using ultrafiltration and chromatographic methods, twelve peptides were purified from the Antarctic Krill hydrolysate and identified as AEK, VEK, VEKT, AEKTR, IEN, VEKGK, LKPGN, IEKG, LQP, ATH, IEKT, and IDSQ. LKPGN and LQP exhibited high scavenging activities on HO·, DPPH·, and O2−·. Moreover, LKPGN and LQP can protect Chang liver cells against H2O2-induced oxidative stress by increasing cell viability and decreasing the apoptosis rate. The mechanism indicated that LKPGN and LQP could concentration-dependently increase the antioxidant enzyme (SOD and GSH-PX) levels to scavenge excess ROS, increase mitochondrial membrane potential, and decrease DNA damage and MDA content. Therefore, LKPGN and LQP from Antarctic Krill could serve as promising candidates applied in health-promoting products.